Tikanga Māori living by Māori values - Mead, Sidney M. 1927- (Huia Publishers, 2016)
"This is an authoritative and accessible introduction to tikanga Māori for people wanting to understand the correct Māori ways of doing things. It covers the ways that tikanga guides relationships between people, people's relationship with the natural environment, spiritual areas, and health, and it proposes guidelines to test appropriate tikanga Māori responses to new situations and challenges in contemporary life"--Publisher information